2019
DOI: 10.1017/s0022215119000434
|View full text |Cite
|
Sign up to set email alerts
|

Surgeons’ preferences and anxiety levels in paediatric adenotonsillectomy: European perspective

Abstract: ObjectiveThis study assessed the preferences of surgeons regarding surgical modalities used for adenotonsillectomy, and determined anxiety levels related to the adenotonsillectomy procedure.MethodsA 10-question survey created by the authors was administered to 413 ENT specialists attending the 4th Congress of Otorhinolaryngology Head and Neck Surgery, held in October 2017 in Barcelona, Spain.ResultsCold knife dissection was the preferred surgical modality for both adenoidectomy and tonsillectomy. Most particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Windfuhr et al reported that the PTH rate was higher in the suture hemostasis group 26 . According to a 10‐question survey completed at a national congress, suture ligating the lower pole and suturing faucial pillars were the main methods surgeons would choose to prevent PTH 27 . Our results showed a significant difference in the incidence of primary PTH between the TIS and TsIS groups.…”
Section: Discussionmentioning
confidence: 56%
“…Windfuhr et al reported that the PTH rate was higher in the suture hemostasis group 26 . According to a 10‐question survey completed at a national congress, suture ligating the lower pole and suturing faucial pillars were the main methods surgeons would choose to prevent PTH 27 . Our results showed a significant difference in the incidence of primary PTH between the TIS and TsIS groups.…”
Section: Discussionmentioning
confidence: 56%
“…Despite this, there remains some morbidity and inherent risks of the procedure. Pain and bleeding remain the top concerns 2,3,6,13,19,27,28 and the number one and two reasons cited for changing techniques 28 …”
Section: Discussionmentioning
confidence: 99%
“…It is a low‐risk procedure with few complications. Postoperative pain is a significant concern, but hemorrhage is the most feared complication due to its association with fatality, especially in pediatric patients with insufficient vascular reserve 2 . Post‐tonsillectomy hemorrhage (PTH) remains the number one complication causing mortality and malpractice settlements, apart from the increased cost of necessary treatment 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anxiety levels experienced by surgeons who perform adenotonsillectomy is a topic that is not often discussed, and is studied even less. The paper from Turkey 4 examines European paediatric ENT surgeons, and finds fair levels of anxiety, particularly with respect to fear of bleeding. This lessens with experience.…”
mentioning
confidence: 99%